PERFORMANCE ANALYSIS OF THERMAL DIODES - Machado, H. A.; Ramos, A. G. (Revista de Engenharia Térmica, 2006)
The thermal diode consists in a common brick empty inside, where the internal cavity is geometrically arranged as two rectangles, disposed one over the other but not aligned. When the lower side is heated, natural convection in the air inside yields high heat transfer rates from this side to the other. When the upper side is heated, the heat transfer should run by pure conduction, and the brick with air inside works as a thermal insulator. As this brick allows a good conductance in one direction and insulation in the opposite sense, it behaves as an electric diode, being known as thermal diode. This principle is already known for a long time, but its use is still not extensive, and there are no basic rules for the cavity design or even a theoretical study of viability for this use replacing the conventional insulation systems. The objective of this work is to simulate the heat transfer process inside a thermal diode, in order to obtain the optimal geometry and dimensions and to verify the viability of its use in buildings for thermal optimization. The numerical data are validated through comparing with that obtained from the test applied to cellular concrete bricks.